Soil erosion in the Xiangxi River Basin based on the RUSLE model - Rao, Wenli; Liu, Zhenxia; Zhang, Qingfeng (DIE ERDE – Journal of the Geographical Society of Berlin, 2023)
The Xiangxi River basin is the largest branch in the upper reaches of Three Gorges Reservoir located in the Hubei prov- ince of China, and it has a significant effect on the storage of the Three Gorges Reservoir. However, soil erosion of the Xiangxi River basin often leads to a series of problems. To minimize the impact of soil erosion on crop production and ecological life, the objective of this study was to evaluate soil erosion of the study area based on the soil and water loss model (RUSLE) with average monthly rainfall data for many years, land-use maps, soil maps, and the remote sensing (RS) images of the Xiangxi River basin and to analyze the spatial characteristics of soil erosion of the study area by geographic information system (GIS) methods in ArcGIS 10.2. The results showed that the areas of a lower grade of ero- sion increased dramatically while the number of the areas of a higher erosion grade decreases relatively compared with the previous study in 2011. This conclusion illustrated that the engineering measures taken by relevant departments affect high grade soil erosion. However, the slope zone of [30, 40) still suffered from high erosion due to mountains with heavy rainfall. It is suggested that more attention should be paid to reduce erosion in mountains, because the Xiangxi River basin belongs to early karst development and large areas of soil are covered with limestone soil. Existing measures to enclose the land for reforestation were not strong enough, thus other measures like planting grass in mountainous areas to alleviate soil erosion should be taken. Meanwhile, for the yellow-brown soil with high erosion, it is necessary to protect soil from stagnant water.